Micropylar and Perimicropylar Regions of the Egg Exochorion in Six Genera of Dismorphiinae (Lepidoptera: Pieridae) - Nieves-Uribe, Sandra; Llorente-Bousquets, Jorge; Flores-Gallardo, Adrián (Zootaxa, 2021)
Using scanning electron microscopy (SEM), we examine and compare the micropylar and perimicropylar regions of the egg exochorion in six genera of the subfamily Dismorphiinae (Pieridae): Leptidea Billberg, Enantia Hübner, Pseudopieris Godman & Salvin, Lieinix Gray, Dismorphia Hübner, and Moschoneura Butler. We provide the first descriptions of the morphological structures of the chorion in these genera. Leptidea is the most primitive genus, and Dismorphia represents the most diverse. We examined the jethys complex of Enantia to study diversity of characters within the genus. We conclude that the exochorion of Dismorphiinae is the most plesiomorphic in relation to Coliadinae and Pierinae, owing to its simple morphology without a transition zone surrounding the wreath (perimicropylar region). Leptidea (Leptideini) shows the least derived characters of the subfamily, followed by Enantia (Dismorphiini). The latter genus exhibits several typical characters of the tribe that are distinctive from other more specialized genera. Exochorionic similarities among the four species of the jethys complex support their close relationship; E. mazai exhibits the most derived features among the species of the complex. Pseudopieris and Moschoneura exhibit several plesiomorphies, such as a large number of openings (micro-grid), but they also show some derived features, such as three semi-rings in the wreath. Dismorphia and Lieinix exhibit characters in their most derived states, such as a striated micro-grid (most conspicuous in Lieinix) and basal aeropyles (most conspicuous in Dismorphia), a character shared with Moschoneura. The purpose of this work is exploratory and descriptive and would be improved by a larger sample size. This contribution is the third in a series of studies on the chorion of Dismorphiinae eggs.